Circulating Histones in Sepsis: Potential Outcome Predictors and Therapeutic Targets - Li, Yupei; Wan, Dingyuan; Luo, Xinyao; Song, Tao; Wang, Yiran; Yu, Qiao; Jiang, Luojia; Liao, Ruoxi; Zhao, Weifeng; Su, Baihai (Frontiers in Immunology, 2021)
Sepsis is defined as a life-threatening organ dysfunction caused by a dysregulated host response to infection and is associated with high morbidity and mortality. Circulating histones (CHs), a group of damage-associated molecular pattern molecules mainly derived from neutrophil extracellular traps, play a crucial role in sepsis by mediating inflammation response, organ injury and death through Toll-like receptors or inflammasome pathways. Herein, we first elucidate the molecular mechanisms of histone-induced inflammation amplification, endothelium injury and cascade coagulation activation, and discuss the close correlation between elevated level of CHs and disease severity as well as mortality in patients with sepsis. Furthermore, current state-of-the-art on anti-histone therapy with antibodies, histone-binding proteins (namely recombinant thrombomodulin and activated protein C), and heparin is summarized to propose promising approaches for sepsis treatment.